Screening for autoimmune diseases in apparently healthy antinuclear antibody positive individuals - Andraos, Rama; Ahmad, Awais; Wirestam, Lina; Dahle, Charlotte; Frodlund, Martina; Rönnelid, Johan; Kastbom, Alf; Sjöwall, Christopher (Frontiers in Medicine, 2024)
Background Anti-nuclear antibodies (ANA) assessed by immunofluorescence (IF) microscopy are associated with systemic autoimmune rheumatic diseases (SARD) and can be detected years before onset of clinical symptoms. Recent data indicate dysregulation of the immune system with increased levels of proinflammatory cytokines, including type I interferons (IFN), in ANA-positive versus ANA-negative individuals. Herein, the aims were to investigate IF-ANA, ANA fine specificities, and IFN-α protein levels in relation to self-reported symptoms, as well as clinical signs, of SARD in a large group of healthy blood donors (HBD). Methods Sera from 825 HBD (48.8% females) were included. IF-ANA was assessed, using HEp-2 cells, according to the routine at the accredited laboratory of Clinical Immunology, Linköping University Hospital. All samples were analyzed for IgG-ANA fine specificities using addressable laser bead assay (ALBIA) at the same laboratory. IFN-α was determined using ELISA. Antibody-positive individuals, and their sex- and age-matched antibody-negative controls, were asked to fill a questionnaire regarding symptoms associated with SARD. Results In total, 130 HBD (15.8%) were positive with IF-ANA and/or ALBIA. Anti-U1RNP was significantly more common among women. Generally, self-reported symptoms correlated poorly with IF-ANA and/or ALBIA results. Two females with high levels of Ro60/SSA, Ro52/SSA and IFN-α reported mild sicca symptoms and were diagnosed with Sjögren’s disease after clinical evaluation. Conclusion A considerable proportion of apparently HBD are autoantibody positive, but without clear association to self-reported symptoms. Nevertheless, the combination of autoantibodies, relevant symptoms and high IFN-α levels identified the small proportion of individuals with SARD in the study population.